2013
DOI: 10.1016/j.oraloncology.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

CD44 interacts with EGFR and promotes head and neck squamous cell carcinoma initiation and progression

Abstract: Objectives CD44 is a promising target for therapy in Head and Neck Squamous Cell carcinoma (HNSCC) and has two defined roles in tumorigenesis: it is a cancer stem cell (CSC) marker and it promotes migration and proliferation through interaction with many signaling molecules. The purpose of this study was to investigate the role of CD44 in HNSCC carcinogenesis. Materials and Methods The effects of CD44 in cell proliferation, migration, apoptosis and cisplatin resistance were studied by its overexpression in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 30 publications
(42 reference statements)
7
58
0
1
Order By: Relevance
“…Chemotherapy resistance is one characteristic of stem-like cancer cells, including in HNSCC (27,28). We observed that our established cisplatin-resistant HNSCC cells with increased G9a also possess more stemness properties than their parental cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Chemotherapy resistance is one characteristic of stem-like cancer cells, including in HNSCC (27,28). We observed that our established cisplatin-resistant HNSCC cells with increased G9a also possess more stemness properties than their parental cells.…”
Section: Discussionmentioning
confidence: 57%
“…Studies have shown that stem-like cancer cells have more ability to resist chemotherapy, including cisplatin (27,28). Thus, we examined whether G9a also contributes to cisplatin resistance in stem-like cancer cells.…”
Section: Depletion Of G9a By Shrna or Enzymatic Inhibitor Sensitizes mentioning
confidence: 97%
“…This result may be associated with another marker, CD44, which was detected in the feces of CRC patients at AJCC stage I. CD44 is of functional importance for tumor initiation and progression in CRC (58). In another animal study, downregulated CD44 was able to reduce tumor growth significantly (59). Recently, CD44 was further proposed to contribute to targeted therapeutic strategies due to its role in sensing the extracellular environment (60).…”
Section: Discussionmentioning
confidence: 90%
“…OSCC is still considered the most common malignancy of the oral cavity and the most lethal cancer due to the late detection of this cancer in its advanced stages despite the easy accessibility of the oral cavity for regular examinations (Perez et al, 2013). Several markers were discovered to correlate the relation between this cancer and CSCs and the role of these cells in tumor aggressiveness, such as CD44 and CD109 (Hema et al, 2014).…”
Section: Discussion:-mentioning
confidence: 99%